Species-specific eDNA markers for rapid detection of invasive fishes in Tasik Raban, Malaysia - Nurul Fizatul Nabilah Osman (2023)
The objective of this study is to develop species-specific environmental DNA (eDNA) markers for Cichla spp. based on mitochondrial cytochrome oxidase I (COI) gene sequences. Validation of the developed species-specific eDNA markers were done exsitu for environmental sample from Tasik Raban. New digital PCR (dPCR) method was also employed to detect the presence of Cichla ocellaris, and Cichla kelberi in environmental water samples. Result from this study showed that COI gene can be used to develop species-specific markers for species Cichla. Ex-situ validation results also showed that the developed markers CO1 amplified specifically to specimen C. ocellaris while CK1 amplified directly to specimen of C. kelberi. In addition, dPCR supported the specificity analysis as absolute fluorescent quantification detected the presence of C. ocellaris and C. kelberi eDNA in water sample at 90% detection confidence. In conclusion, CO1 and CK1 markers were successfully developed and specific to be used as eDNA markers for C. ocellaris and C. kelberi respectively. As an implication, eDNA analysis with species-specific markers suitable to be used as new rapid monitoring tool in detection of invasive species for biodiversity management and conservation purposes.